Kinetics of Phenol Biodegradation by Heavy Metal Tolerant Rhizobacteria Glutamicibacter nicotianae MSSRFPD35 From Distillery Effluent Contaminated Soils - Duraisamy, Purushothaman; Sekar, Jegan; Arunkumar, Anu D.; Ramalingam, Prabavathy V. (Frontiers in Microbiology, 2020)
Biodegradation of phenol using bacteria is recognised as an efficient, environmentally friendly and cost-effective approach to reducing phenol pollutants compared to the current conventional physicochemical processes adopted. A potential phenol degrading bacterial strain Glutamicibacter nicotianae MSSRFPD35 was isolated and identified from Canna indica rhizosphere grown in distillery effluent contaminated sites. It showed high phenol degrading efficiency upto 1117 mg L-1 within 60 h by the secretion of catechol 1,2-dioxygenase via ortho intradial pathway. The strain MSSRFPD35 possess both the catechol 1,2 dioxygenase and catechol 2,3 dioxygenase coding genes that drive the ortho and meta pathways, but the enzymatic assay revealed that the strain cleaves catechol using ortho pathway. Haldane’s kinetic method was well fit to exponential growth data and the following kinetic parameter was obtained: µ*= 0.574h-1, Ki=268.1, Ks=20.29 mg L-1. The true µmax and Sm calculated was 0.37 h-1 and 73.76 mg L-1 respectively. The Haldane’s constant values were similar to earlier studies and healthy fitness depicted in correlation coefficient value R2 of 0.98. Phenol degrading kinetic’s predicted using Haldane’s model as qmax 0.983, Ki′ 517.5 and Ks′ 9.152. Besides, MSSRFPD35 was capable of utilizing different monocyclic and polycyclic aromatic hydrocarbons and degrades phenol in the presence of different heavy metals. This study for the first time reports high phenol degrading efficiency of G. nicotianae MSSRFPD35 in the presence of toxic heavy metals. Thus, the strain G. nicotianae MSSRFPD35 can be exploited for the bioremediation of phenol and its derivatives polluted environments, co-contaminated with heavy metals.